Metabolic Syndrome: Development of the Issue, Main Diagnostic Criteria - Yu. N. Belenkov; E. V. Privalova; V. Y. Kaplunova; V. Y. Zektser; N. N. Vinogradova; I. S. Ilgisonis; G. A. Shakaryants; M. V. Kozhevnikova; A. S. Lishuta (Рациональная фармакотерапия в кардиологии)
Obesity is one of the leading and the most serious risk factors of cardiovascular diseases. Overweight provokes many metabolic and hemodynamic disorders.  About 30% of inhabitants of the planet have overweight and prevalence of obesity increases by 10% every 10 years according to the WHO data.  The probability of arterial hypertension in obese  patients is 50% higher than in people with normal body mass. Framingham study showed that obesity is an independent, significant risk factor  of ischemic heart  disease, myocardial infarction, cerebral stroke  and  diabetes mellitus. The most dangerous is the central obesity with the preferential fat deposition in the abdomen. Combination of visceral obesity, violation of carbohydrate and lipid metabolism, arterial hypertension, and close pathogenic relationship between these  factors  underlie the isolated symptom complex known  as metabolic syndrome. J. Vague was the first to describe relationship between abdominal obesity with cardiovascular disease and mortality in 1947. In our country G.F. Lang noticed common combination of arterial hypertension with obesity, lipid and carbohydrate metabolism disorders. Thus, metabolic syndrome significantly increases risk and  severity of cardiovascular disease. Within last decades criteria of metabolic syndrome stays constant. The factors  of insulin resistance and  endothelial dysfunction as stages of the pathogenesis of the metabolic syndrome have been  studied in detail. The mechanisms of insulin resistance and endothelial dysfunction are discussed in detail in this article as well as inflammatory markers and the significance of highly sensitive C-reactive protein.